ALE‐FEM for Two‐Phase Flows. Issue 1 (December 2013) - Hahn, Andreas; Held, Kristin; Tobiska, Lutz
Abstract We present a finite element method for the flow of two immiscible incompressible fluids in two and three dimensions. Thereby the presence of surface active agents (surfactants) on the interface is allowed, which alter the surface tension. The model consists of the incompressible Navier‐Stokes equations for velocity and pressure and a convection‐diffusion equation on the interface for the distribution of the surfactant. A moving grid technique is applied to track the interface, on that account a Arbitrary‐Lagrangian‐Eulerian (ALE) formulation of the Navier‐Stokes equation is used. The surface tension force is incorporated directly by making use of the Laplace‐Beltrami operator technique [5]. (© 2013 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)